2013
DOI: 10.1038/jhg.2013.76
|View full text |Cite
|
Sign up to set email alerts
|

Galactosemia in the Turkish population with a high frequency of Q188R mutation and distribution of Duarte-1 and Duarte-2 variations

Abstract: Classical galactosemia is an inherited recessive disorder of galactose metabolism caused by deficiency of the enzyme galactose-1-phosphate uridyl transferase (GALT), which is caused by mutations in the GALT gene. In this study, 56 Turkish patients diagnosed with galactosemia were screened for GALT gene mutations using Affymetrix resequencing microarrays. Eleven types of mutations were detected in these patients, including two novel mutations (R258G and G310fsX49) and nine recurrent mutations. We detected six p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…While the analysis of gene mutations was out of scope of the current study, it is of paramount value to study type of mutations in Egyptian children with galactosemia. The mutation-phenotype is different ethnic groups [32] , [33] , [34] , [35] , [36] , [37] , and the functional correction of gene defect is currently studied. The specific gene mutation analysis and functional correction expands the management opportunities of galactosemia from galactose restriction to gene therapy [38] .…”
Section: Discussionmentioning
confidence: 99%
“…While the analysis of gene mutations was out of scope of the current study, it is of paramount value to study type of mutations in Egyptian children with galactosemia. The mutation-phenotype is different ethnic groups [32] , [33] , [34] , [35] , [36] , [37] , and the functional correction of gene defect is currently studied. The specific gene mutation analysis and functional correction expands the management opportunities of galactosemia from galactose restriction to gene therapy [38] .…”
Section: Discussionmentioning
confidence: 99%
“…(Leu218 = );c.940A>G/ p.(Asn314Asp)], was first reported in 1995, from Turkey (Gathof et al., 1995). Later, in a study of 56 patients also from Turkey, D1 was found to be in linkage disequilibrium with the c.1018G>T/ p.(Glu340 * )in all 12 alleles of the patients carrying this variant, suggesting that it arose from a common ancestor (Özgül et al., 2013). In our study, 18 alleles were in linkage disequilibrium with D1, but four co‐segregated with Duarte variant only (c.940A>G/p.…”
Section: Discussionmentioning
confidence: 99%
“…Özgür et al. detected that variations on exons 6 and 10 of the GALT gene account for 79% of all disease‐related alleles in the Turkish population, and besides variation detection rate was 97.3% (Özgül et al., 2013). Meanwhile, Calderon et al.…”
Section: Discussionmentioning
confidence: 99%
“…While compound heterozygous patients are widely encountered in relatively more common diseases such as biotinidase deficiency or phenylketonuria (Karaca et al, 2015;Unal et al, 2015), rarer autosomal recessive disorders (eg. methylmalonic acidaemia, primary carnitine deficiency, galactosaemia) occur almost exclusively in patients with homozygous variants from consanguineous families (Dundar et al, 2012;Kilic et al, 2012;Ozgul et al, 2013). These observations led us to hypothesize that the detected PMM2 variants might have a high allele frequency in Turkey, and to try to test this hypothesis in an in-house exome database.…”
Section: Discussionmentioning
confidence: 99%